2009
DOI: 10.1002/stem.190
|View full text |Cite
|
Sign up to set email alerts
|

Depot-Specific Differences in Adipogenic Progenitor Abundance and Proliferative Response to High-Fat Diet

Abstract: White adipose tissue (fat) is the primary organ for energy storage and its regulation has serious implications on human health. Excess fat tissue causes significant morbidity, and adipose tissue dysfunction caused by excessive adipocyte hypertrophy has been proposed to play a significant role in the pathogenesis of metabolic disease. Studies in both humans and animal models show that metabolic dysfunction is more closely associated with visceral than subcutaneous fat accumulation. Here, we show that in mice fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(230 citation statements)
references
References 30 publications
11
214
1
4
Order By: Relevance
“…eWAT was excised and analyzed as described previously (21,52), with minor modifications. Tissues were minced in PBS and digested with collagenase (Worthington Biochemical Corporation) (1 mL/g of homogenized tissue) at 37°C for 2 h. Cells were collected by centrifugation at 200 × g for 10 min, and the floating adipocyte layer and supernatant discarded.…”
Section: Methodsmentioning
confidence: 99%
“…eWAT was excised and analyzed as described previously (21,52), with minor modifications. Tissues were minced in PBS and digested with collagenase (Worthington Biochemical Corporation) (1 mL/g of homogenized tissue) at 37°C for 2 h. Cells were collected by centrifugation at 200 × g for 10 min, and the floating adipocyte layer and supernatant discarded.…”
Section: Methodsmentioning
confidence: 99%
“…S5A), whereas preadipose cells in postnatal BAT and WAT were Sca1 + (Fig. S5B) (28,29). Quantitative PCR (qPCR) analysis revealed that Pparγ and Zfp423, key adipocyte-lineage genes (30,31), were expressed at higher levels in Myf5 Cre (GFP) + ; Pdgfrα + cells relative to other sorted fractions (Fig.…”
Section: Ebf2 Expression Identifies Brown Preadipose Cells During Devmentioning
confidence: 97%
“…The following monoclonal primary antibodies were used: anti-CD31 (clones MEC13.3, Becton Dickenson, Mississauga, Canada, www.bd.com, and 390; Cedarlane Laboratories, Burlington, Canada, https://pilot.cedarlanelabs.com), anti-CD34 (clone RAM34; eBioscience), anti-CD45 (clone 30-F11; Becton Dickenson), anti-Sca-1 (clone D7; eBiosciences, San Diego, California, www.ebiosciences.com), and anti-a7 integrin (produced inhouse). The antibody dilutions were as previously reported [9,12]. Analysis was performed on LSRII (Becton Dickenson) equipped with three lasers.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…In order to isolate NCderived adipocyte progenitors, we dissected and enzymatically dissociated the cephalic, flank, and perigonadal fat depots from WNT1-Cre/R26-YFP mice to separate the stromal vascular component. To identify prospective NC-derived adipocyte progenitors, we followed a flow cytometry strategy previously developed to identify WAT progenitors in mesodermal fat depots [9]. We first excluded cells from hematopoietic, endothelial, and myogenic lineages by gating the stromal vascular fraction (SVF) based on the expression of CD45 (hematopoietic), CD31 (endothelial), and a 7 integrin (skeletal/smooth muscle) ( Fig.…”
Section: Nc-derived Linmentioning
confidence: 99%
See 1 more Smart Citation